The agriculture-nutrition nexus in Kiribati - Otiuea, T.; Teariki-Ruatu, N.; Timeon, E.; Francis, Judith Ann; Dietershagen, Jana (Technical Centre for Agricultural and Rural Cooperation, 2019)
Kiribati is estimated to need 50% more food by 2030 to feed its growing population. Extreme weather conditions and rising sea levels threaten agricultural production and livelihoods.Overfishing and unregulated commercial development are reducing: Sea cucumber, seaweed and tuna among others are becoming extinct. High dependency on imported foods is changing food tastes and reducing consumption of nutrient dense local foods e.g. giant taro, pandanus and fish. This Technical Brief describes the problems and proposes recommendations to solve them.